The genus Pholetesor Mason, 1981 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eleven new species - Liu, Zhen; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2016)
The genus Pholetesor Mason from China is revised. Eleven new species are described and illustrated, namely P. acricauda Liu & Chen, sp. n., P. argyresthiae Liu & Chen, sp. n., P. artusisulcus Liu & Chen, sp. n., P. confusus Liu & Chen, sp. n., P. flavigleba Liu & Chen, sp. n., P. flaviparvus Liu & Chen, sp. n., P. lithocolletis Liu & Chen, sp. n., P. lyonetiae Liu & Chen, sp. n., P. spinadensus Liu & Chen, sp. n., P. taiwanensis Liu & Chen, sp. n., and P. teresitergum Liu & Chen, sp. n. Six species are newly recorded in China, namely P. arisba (Nixon, 1973), P. circumscriptus (Nees, 1834), P. laetus (Marshall, 1885), P. maritimus (Wilkinson, 1941), P. salalicus Mason, 1959 and P. viminetorum (Wesmael, 1837). A key to the Chinese species of this genus is provided.